71 Evaluation of the CVDS Beef Cow Model to Estimate Biological Efficiency in Mature Cows. (7th May 2021) - Lancaster, Phillip A; Davis, Mike; Tedeschi, Luis O; Rutledge, Jack; Cundiff, Larry
Abstract: There is no clear method to measure biological efficiency in grazing beef cows. The objective of this study was to evaluate a nutrition model to estimate biological efficiency in mature cows. Data from dams (n = 160) and their 2 nd and 3 rd progeny were collected from 1953 through 1980. Individual feed intake was measured at 28-d intervals for lifetime of dams and during 240-d lactation for progeny. Body weight of progeny were measured at birth and weaning, and dams at parturition and weaning each production cycle. Milk yield of dams was measured at 14-d intervals by hand milking. Metabolizable energy required (MER) and predicted milk energy yield (MEY) of each cow was computed using the CVDS beef cow model for each parity. Biological efficiency was computed as the ratio of cow ME intake (MEI) to calf weaning weight (WW) based on observed (MEI/WW) and predicted (MER/WW) values. Pearson correlation coefficients were computed using corr.test function in R software. Average (SD) cow weight, calf weaning weight, cow MEI, and observed MEY were 507 (81) and 548 (88) kg, 287 (49) and 294 (44) kg, 9406 (2695) and 9721 (2686) Mcal, and 1009 (538) and 1051 (521) Mcal, for progeny 2 and 3, respectively. Cow MEI and MER (0.87 and 0.85), and observed and predicted MEY (0.51 and 0.51) were positively correlated for progeny 2 and 3, respectively. The CVDS model under predicted cow MEI [mean bias = 1685 (1718) and 1658 (1702) Mcal] and MEY [mean bias = 82 (465) and 129 (450) Mcal] for progeny 2 and 3, respectively. Observed and predicted progeny feed intake were not correlated. Observed and predicted biological efficiency were positively correlated (0.63 and 0.61) for progeny 2 and 3, respectively. In conclusion, nutrition models can reasonably predict biological efficiency, but further refinement of the relationship between calf feed intake and milk yield could improve prediction.